2022
DOI: 10.7575/aiac.ijkss.v.10n.4p.16
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent Knee Joint Isokinetic Profile in Professional Male Soccer Players

Abstract: Background: The knee-joint isokinetic profile (KJIP) injury risk factor may be modulated by chronological age, however, comparative data for elite male soccer players aged 25 years and older is lacking. Objective: To describe and compare the knee-joint isokinetic profile (KJIP) according to the chronological age of professional male soccer players. Method: In a cross-sectional study design, sixty-three soccer athletes from the first Chilean soccer division (A-series) were divided into younger and older groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…These results are again consistent with a recent study [43] that confirmed the same relationships by analyzing the same isokinetic strength variables at the same angular velocities and comparing professional soccer players with elite academy players (U-19). The age-related discrepancy in isokinetic muscle strength variables in soccer players may be due to the differences in factors such as players' competition levels, testing period, training load, number of matches played, and strength training regimes [4,44].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…These results are again consistent with a recent study [43] that confirmed the same relationships by analyzing the same isokinetic strength variables at the same angular velocities and comparing professional soccer players with elite academy players (U-19). The age-related discrepancy in isokinetic muscle strength variables in soccer players may be due to the differences in factors such as players' competition levels, testing period, training load, number of matches played, and strength training regimes [4,44].…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, the present results reveal that the TW-Q and TW-H variables are higher for seniors than for juniors, meaning that seniors produce more work with quadriceps and hamstrings than juniors. In the context of an isokinetic muscular contraction, total work depicts the muscle's ability to generate strength over the entire range of movement [44]. Over the same joint amplitude, seniors are thus able to produce greater work than juniors with the knee flexor and extensor muscles.…”
Section: Plos Onementioning
confidence: 99%